2015
DOI: 10.1128/genomea.00882-15
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequences of Low-Passage Virulent and High-Passage Avirulent Variants of Pathogenic Leptospira interrogans Serovar Manilae Strain UP-MMC-NIID, Originally Isolated from a Patient with Severe Leptospirosis, Determined Using PacBio Single-Molecule Real-Time Technology

Abstract: Here, we report the complete genome sequences of low-passage virulent and high-passage avirulent variants of pathogenic Leptospira interrogans serovar Manilae strain UP-MMC-NIID, a major causative agent of leptospirosis. While there were no major differences between the genome sequences, the levels of base modifications were higher in the avirulent variant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 14 publications
(15 reference statements)
0
27
0
Order By: Relevance
“…Analyses can be performed using IPD ratios of cases versus controls or vs an in silico control compared to known epigenetics signatures for 6-mA, 4-mC and (Tet converted) 5-mC (available in SMRT analysis). This has been used to discriminate virulent from avirulent Leptospira interrogans, a cause of leptospirosis in humans ( 90 ). The genome sequences have no major differences between strains, but higher levels of methylation are found in the avirulent strain ( 90 ).…”
Section: Viral and Microbial Medical Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…Analyses can be performed using IPD ratios of cases versus controls or vs an in silico control compared to known epigenetics signatures for 6-mA, 4-mC and (Tet converted) 5-mC (available in SMRT analysis). This has been used to discriminate virulent from avirulent Leptospira interrogans, a cause of leptospirosis in humans ( 90 ). The genome sequences have no major differences between strains, but higher levels of methylation are found in the avirulent strain ( 90 ).…”
Section: Viral and Microbial Medical Sequencingmentioning
confidence: 99%
“…This has been used to discriminate virulent from avirulent Leptospira interrogans, a cause of leptospirosis in humans ( 90 ). The genome sequences have no major differences between strains, but higher levels of methylation are found in the avirulent strain ( 90 ). Methylation analysis has also been used to identify virulence factor genotype-dependent motifs in eight different H. pylori strains, a bacteria that can lead to gastrointestinal diseases ( 91 ).…”
Section: Viral and Microbial Medical Sequencingmentioning
confidence: 99%
“…Significantly up-and down-regulated ncRNAs upon 1h exposure to 1 mM H 2 O 2 with a Log 2 FC cutoff of 1.5. Gene numeration is according to to Satou et al(52). * ORFs significantly up-regulated by RNASeq analysis (Log 2 FC cutoff of 1).…”
mentioning
confidence: 99%
“…These findings could lead to the development of antimicrobials for leptospirosis targeting the pathogens’ adhesion and crawling motility and provides a significant step forward to confront other host-dependent bacterial infections. Meanwhile, microarray analyses have revealed that regulation of gene expression in Leptospira is affected by its interaction with host cells 27,28 . Although host immune responses against Leptospira infection remain mostly unknown, pathogenic leptospires interfere with the complement system through the degradation of complement proteins 29 and inhibition of coagulation via binding to thrombin 30 .…”
Section: Figmentioning
confidence: 99%